Semiannual versus annual influenza vaccination in older adults in the Tropics: an observer-blind, active-comparator-controlled, randomized superiority trial - Young, Barnaby; Wilder-Smith, Annelies (Clinical infectious diseases, 2019)
Background: Antibody titres and vaccine effectiveness decline within 6 months after influenza vaccination in older adults. Biannual vaccination may be necessary to provide year-round protection in the tropics, where influenza circulates throughout the year. Methods: Tropical Influenza Control Strategies (TROPICS1) was a single-center, 1:1 randomized, observer-blinded, active-comparator–controlled, superiority study in 200 community-resident adults aged ≥65 years. Participants received a standard-dose trivalent inactivated influenza vaccination (IIV3) at enrollment, and either tetanus-diphtheria-pertussis vaccination or IIV3 6 months later. The primary outcome was the proportion of participants with haemagglutination-inhibition (HI) geometric mean titre (GMT) ≥1:40 1 month after the second vaccination (month 7). Secondary outcomes included GMTs to month 12, the incidence of influenza-like illness (ILI), and adverse reactions after vaccination. Results: At month 7, the proportion of participants with an HI tire ≥1:40 against A/H1N1 increased by 21.4% (95% confidence interval [CI] 8.6–33.4) in the semiannual vaccination group. This proportion was not significantly higher for A/H3N2 (4.3, 95% CI -1.1–10.8) or B (2.1, 95% CI -2.0–7.3). Semiannual vaccination significantly increased GMTs against A/H1N1 and A/H3N2, but not B, at month 7. Participants receiving a repeat vaccination of IIV3 reported a significantly lower incidence of ILI in the 6 months after the second vaccination (relative vaccine effectiveness 57.1%, 95% CI 0.6–81.5). The frequency of adverse events was similar after the first and second influenza vaccinations. Conclusions: Semiannual influenza vaccination in older residents of tropical countries has the potential to improve serological measures of protection against infection. Alternative vaccination strategies should also be studied. Clinical Trials Registration NCT02655874.
Published: 01 October 2018
Gesehen am 21.10.2019